Some Theological Issues around Child Protection - Reid, Duncan (Journal of Anglican studies, 2006)
This short piece seeks to offer a theological framing to the issues raised by Garth Blake in his very fine article ‘Child Protection and the Anglican Church of Australia’. What are some of the theological issues behind the current state of affairs with regard to child protection, and the church's attempts to remedy past failures to protect the children in its care? Very briefly I want to mention several clusters of theological issues: responsibility, or the duty of care; forgiveness and betrayal of trust; sin and scapegoating; gospel and law; and the problem of meaning.